TRADISI RITUAL ADAT TULUDE DI KELURAHAN WANGURER BARAT KECAMATAN MADIDIR KOTA BITUNG - Jimmy Carter Nicodemus (Universitas Sam Ratulangi, 2023)
North Sulawesi Province consists of three major tribes, namely the Minahasa, Sangihe Talaud and Bolaang Mongondow. The three tribes/ethnicities have sub-ethnicities that have different languages and traditions. North Sulawesi Province has several regional languages such as Toulour, Tombulu, Tonsea, Tontembuan, Tonsawang, Ponosakan, and Bantik (from the Minahasa tribe), Sangihe, Siau, Talaud (from Sangihe and Talaud), and Mongondow, Bolaang, Bintauna, Kaidipang (from Bolaang Mongondow). Not only language, culture is also very diverse such as art and culture passed down by ancestors in descending generations. Tulude or kunci taong (key of the year) is held at the end of every January and is filled with traditional ceremonies of a religious nature. Tulude traditional ritual or in Sangir Mandullu'u Tonna language is one of the cultures of the Indonesian nation that is still maintained, fostered and developed by the Sangihe and Talaud people until now experiencing development into a regional cultural art performances. This Tulude traditional ritual ceremony is a tradition of North Nusa residents who live in Bitung City, Tulude by the residents of North Nusa is a traditional year-end party that is a routine activity that is almost carried out by North Nusa residents throughout the Bitung City area. This traditional ceremony is always performed annually at the end of January as an expression of gratitude to God as a form of His care and inclusion in their lives. Keywords: Ritual, year key, tulude